Patients with inflammatory bowel disease (IBD) prefer oral tablets over other modes of medicine administration. (2nd September 2021) - Denesh, Deepa; Carbonell, Jenelyn; Kane, John S; Gracie, David; Selinger, Christian P.
ABSTRACT: Objectives : With increasing treatment choices for inflammatory bowel disease (IBD), patients' preferences should be considered to limit non-adherence. We explored patients' preferences for route, form and frequency of medication administration, and factors influencing these choices. Methods : Patients rated acceptability of different forms of medication on 10-point Likert scales and preferences for highest acceptable frequency. Results : Of 298 patients significantly more found tablets (91%) to be highly acceptable compared to granules (64%), infusions (33%) and subcutaneous injections (34%; p < 0.0001). The acceptable frequency for tablets was considered as daily by 63.5% and several times daily by 32.3%. Participants preferred nurse delivered over self-administered injections (median score 8 vs 5, p < 0.0001) and hospital-based infusions over infusions at home (median score 7 vs 5, p = 0.001). Patients with previous or current anti-TNF exposure were more accepting of self-administered injections (50.5% vs 23.3% anti-TNF naive; p < 0.001), more accepting of home based infusions (43.7% vs 28.0%; p = 0.001) and more accepting of hospital-based infusions (57.2% vs 37.8%; p = 0.02). Conclusion : Most patients with IBD prefer tablets. Those patients who already experienced biological agents, had a high level of acceptance for subcutaneous and intravenous forms of medication.